Zero Waste Program (Through Kang Pisman School) as an Implementation of Environmental Love Education at Insan Madani Islamic Boarding School - Nasir, Tatang Muh; Hasbiyallah, Hasbiyallah; Pebriansyah, Ilham Arif; Dedih, Ujang (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The research background is based on the problem of low waste management in the city of Bandung. Waste management is important because the accumulation of waste results in various bad things that have an impact on people's health and the environment. The aim of the research is to obtain a description of the Zero Waste program (through the Kang Pisman School) and to find out the Implementation of Love the Environment Education implemented in the Insan Madani Islamic boarding school. Collecting data from research using observation and interview techniques. This research uses a quantitative approach with descriptive research methods. The object of this research is the Insan Madani Islamic Boarding School Santri. The results of the research show that the Zero waste program (Through the Kang Pisman school) is suitable for students at the Insan Madani Islamic Boarding School. Because, through this zero waste program, students will know how to reduce, separate, and utilize what is there. After the students get used to doing